Analysis Of Restorative Justice On Fraud And Embezzlement Crimes In Coffee Trading At The Directorate Of General Criminal Investigation Lampung Regional Police (SPPP Study Number: SPPP/31/I/RES.1.11/2025/Ditreskrimum) - Erlina B; Hendri Novriko (International Journal of Education, Vocational and Social Science, 2026)
The General Criminal Investigation Directorate of the Lampung Regional Police handles criminal acts of fraud and embezzlement which are resolved through a restorative justice mechanism, where the perpetrator is given the opportunity to admit his mistake, repair the victim's losses, and rebuild disturbed social relationships. The research problem is what are the factors causing the occurrence of criminal acts of fraud and embezzlement in coffee sales and how restorative justice is applied to criminal acts of fraud and embezzlement in coffee sales at the General Criminal Investigation Directorate of the Lampung Regional Police. The research method in this study is a normative juridical approach and an empirical approach and is concluded by deductive thinking so that it becomes a general picture of the answer to the problem based on the research results. The results of the study indicate the factors causing the occurrence of criminal acts of fraud and embezzlement in coffee sales arises from a combination of psychological and financial pressure, weak supervision, and the perpetrator's ability to justify their actions. Crime occurs when pressure, opportunity, and rationalization converge. The application of restorative justice to the crime of fraud and embezzlement in coffee sales at the Lampung Regional Police's General Criminal Investigation Directorate was effective in restoring relationships between the perpetrator, victim, and community. This approach is in accordance with Braithwaite's theory of reintegrative shaming, where shame is directed at the act, not the perpetrator's identity, so that the perpetrator can still be reintegrated into society. Recommendations: Companies and business actors are advised to strengthen internal supervision and transaction administration systems. Increasing legal education and individual awareness of the consequences of criminal acts needs to be done routinely. In implementing restorative justice, the Lampung Regional Police's General Criminal Investigation Directorate is advised to continue to facilitate a fair and transparent mediation process between the perpetrator, victim, and community. Police officers need to emphasize the principle of reintegrative shaming, by directing shame at the act, not the perpetrator's identity, so that the perpetrator can continue to participate in social and economic activities.